2022
DOI: 10.1155/2022/2214686
|View full text |Cite
|
Sign up to set email alerts
|

circ-0007707/miR-429/PDGFD Pathway Regulates the Progression of Gastric Cancer by Modulating the Immune-Gene Signature

Abstract: Background. Immunotherapy is an important treatment modality for gastric cancer, therefore, it is crucial to understand the regulators of the tumor microenvironment in gastric cancer. Numerous studies have shown that noncoding RNAs have a critical status in the tumor progression, and the influence of competing endogenous RNA (ceRNA) networks on gastric adenocarcinoma has been widely discussed over the years, but the connection between ceRNA networks and the immune microenvironment of cancer is unclear. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…No association between these 10 genes and acne has been reported before. In gastric cancer, PDGFD regulates the immune microenvironment by modulating the immune genes TAB1 and CXCR4 , while lipopolysaccharide (LPS) induced inflammation is mediated by CXCR4 , which binds bacterial LPS [ 28 , 29 ]. Severe acne can cause infiltration of inflammatory cells and severe inflammation response under the irritation of Cutibacterium acnes ( C. acnes ).…”
Section: Discussionmentioning
confidence: 99%
“…No association between these 10 genes and acne has been reported before. In gastric cancer, PDGFD regulates the immune microenvironment by modulating the immune genes TAB1 and CXCR4 , while lipopolysaccharide (LPS) induced inflammation is mediated by CXCR4 , which binds bacterial LPS [ 28 , 29 ]. Severe acne can cause infiltration of inflammatory cells and severe inflammation response under the irritation of Cutibacterium acnes ( C. acnes ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although a number of circRNAs, functioning as oncogenes or tumor suppressors, have been reported to be involved in STAD progression [ 28 31 ], no studies have so far addressed circ_0000182’s role in STAD. Furthermore, there has been a few recent studies presenting that circRNAs have a strong ability to participate in regulating cholesterol metabolism in non-tumor cells, such as macrophages and aortic endothelial cells [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CeRNA networks based on circRNAs have an impact on the occurrence and development of gastrointestinal cancers [ 40 ]. Furthermore, it has been found that circRNAs acted as ceRNAs for miRNAs to regulate proliferation of STAD cells [ 28 , 31 ]. Interestingly, lncRNA‐TTN‐AS1 was found to act as a ceRNA for miR‐133b to regulate the expression of SQLE in pancreatic cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we first identified 36 OSRGs that are associated with STAD prognosis and the functions of these genes in STAD have been gradually elucidated in recent years. For instance, the elevated expression of the platelet-derived growth factor D (PDGFD) was proved to be an indicator for a poor prognostic outcome of patients with gastric cancer (GC) ( 13 ), and the PDGFD-related immune-gene signature was regarded as a moderator to guide immunotherapy programs. Glutathione peroxidase 3 (GPX3) has been confirmed to prevent migration and invasion in GC via NF-κB/Wnt5a/JNK signaling ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that OSRGs are predictive of cancers such as gliomas (9), bladder cancer (10), and prostate cancer (11). The potential role of OSRGs in the tumorigenesis and progression of STAD has been gradually demonstrated by growing evidence (12)(13)(14)(15). Nonetheless, limited knowledge is available about the molecular pattern of OSRGs in STAD and the link of OSRGs with clinical features, immune landscape, and response to immunotherapy, and drug sensitivity.…”
Section: Introductionmentioning
confidence: 99%